Early Biofilm Formation on UV Light Activated Nanoporous TiO2 Surfaces In Vivo - Areid, Nagat; Söderling, Eva; Tanner, Johanna; Kangasniemi, Ilkka; Närhi, Timo O. (International Journal of Biomaterials, 2018)
Purpose. To explore early S. mutans biofilm formation on hydrothermally induced nanoporous TiO2 surfaces in vivo and to examine the effect of UV light activation on the biofilm development. Materials and Methods. Ti-6Al-4V titanium alloy discs (n = 40) were divided into four groups with different surface treatments: noncoated titanium alloy (NC); UV treated noncoated titanium alloy (UVNC); hydrothermally induced TiO2 coating (HT); and UV treated titanium alloy with hydrothermally induced TiO2 coating (UVHT). In vivo plaque formation was studied in 10 healthy, nonsmoking adult volunteers. Titanium discs were randomly distributed among the maxillary first and second molars. UV treatment was administered for 60 min immediately before attaching the discs in subjects’ molars. Plaque samples were collected 24h after the attachment of the specimens. Mutans streptococci (MS), non-mutans streptococci, and total facultative bacteria were cultured, and colonies were counted. Results. The plaque samples of NC (NC + UVNC) surfaces showed over 2 times more often S. mutans when compared to TiO2 surfaces (HT + UVHT), with the number of colonized surfaces equal to 7 and 3, respectively. Conclusion. This in vivo study suggested that HT TiO2 surfaces, which we earlier showed to improve blood coagulation and encourage human gingival fibroblast attachment in vitro, do not enhance salivary microbial (mostly mutans streptococci) adhesion and initial biofilm formation when compared with noncoated titanium alloy. UV light treatment provided Ti-6Al-4V surfaces with antibacterial properties and showed a trend towards less biofilm formation when compared with non-UV treated titanium surfaces.